Quercetin inhibits intestinal non-haem iron absorption by regulating iron metabolism genes in the tissues - Lesjak, Marija; Balesaria, Sara; Skinner, Vernon; Debnam, Edward S.; Srai, Surjit Kaila S. (European journal of nutrition, 2019)
Purpose There is general agreement that some dietary polyphenols block non-haem iron uptake, but the mechanisms by which they achieve this action are poorly understood. Since the polyphenol quercetin is ingested daily in significant amounts, we have investigated the effect of quercetin on duodenal non-haem iron absorption in vivo, as well as its effect on factors known to be involved in systemic iron metabolism. Methods Rats were subject to gastric gavage and systemic quercetin administration. Treatments were followed with uptake studies using radiolabeled iron, serum iron and transferrin saturation measurements, LC-MS/MS analysis of quercetin metabolites in serum, determination of tissue non-haem iron content and analysis of gene expression of iron-related proteins. Results Both oral and intraperitoneal (IP) quercetin caused serum and tissue iron depletion by two means, first by increasing mucosal iron uptake and inhibiting iron efflux from duodenal mucosa, and second by decreasing levels of duodenal DMT1, Dcytb and FPN. Additionally, IP quercetin induced highly significant increased liver expression of hepcidin, a hormone known to inhibit intestinal iron uptake. Conclusions Oral quercetin significantly inhibited iron absorption, while IP quercetin significantly affected iron-related genes. These results could lead to development of new effective ways of preventing and treating iron deficiency anaemia, the most widespread nutritional disorder in the world.